PEMANFAATAN APLIKASI DISCORD SEBAGAI ALTERNATIF PEMBELAJARAN BIPA DARING - Helmi Muzaki; Caesar Adlu Hakim (STKIP PGRI SUMENEP, 2022)
The Covid-19 pandemic has made learning that was initially carried out offline become online. Although several educational institutions have started to carry out offline learning now learning Indonesian for Foreign Speakers (BIPA) is still being carried out online. In online learning, BIPA teachers need applications that can be used both synchronously and asynchronously. Discord is an application that can be used in BIPA learning both synchronously and asynchronously. This study aims to describe the Discord application as an alternative in online BIPA learning and describe the use of Discord in online BIPA learning. The method used is library research. The data in this study are in the form of national, international journal articles, books, and references that are relevant to the use of Discord as an online BIPA learning medium. The results of this study indicate that Discord has features that support online BIPA learning. Therefore, Discord can be used as a medium in online BIPA learning. These features include Roles, Text Channels, Voice Channels, Video Conferences, and Bots. This study also shows the use of Discord in online BIPA learning with four basic language skills, namely listening, speaking, reading, and writing.